Chemosensory Exploitation and Predator-Prey Arms Races - Richard K. Zimmer (Frontiers Media S.A., 2021)
Thousands of armed predatory species, distributed widely across the metazoan tree-of-life, consume only hard-shell or exoskeleton-bearing organisms (called “durophagy”). Prey armor clearly has evolved in response to selection by predators, but there is little evidence of the contrary, counter-adaptation by predators. Evolved consumer responses to prey, in general, might be more readily expressed in ways other than morphological traits, including via sensory cues. Here, we explored the chemosensory basis for durophagy in a model predator-prey system, and identified intimate associations between durophagous predators and their shelled prey. Barnacles (Balanus glandula and Semibalanus cariosus) bear hard shells and secrete, respectively, a 199 or 201 kDa glycoprotein ortholog (named “MULTIFUNCin”), with expression limited to the body armor (epidermis, cuticle, and live shell). To test for effects of MULTIFUNCin on predators, we constructed faux prey to mimic meaningful physical and chemical characteristics of live barnacles. In separate experiments, each consumer species was presented MULTIFUNCin, purified from either B. glandula or S. cariosus, at a typical armor concentration. All six predatory species (sea star, Pisaster ochraceus; whelks, Acanthinucella spirata, Nucella emarginata, N. ostrina, N. canaliculata, and N. lamellosa) attacked and ate MULTIFUNCin-infused faux prey significantly more than controls. Akin to barnacles, secretion of glycoprotein-rich extracellular matrices is common among armored prey species—from marine sponges to terrestrial vertebrates. Our results, therefore, suggest that chemosensory exploitation of glycoproteins could be widespread, with notable consequences for life on land and in the sea.